The relevance of judicial procedure for economic growth - Bernd Hayo; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2008)
It has been argued that procedural formalism undermines economic efficiency by fostering rent-seeking and corruption. We challenge this view by arguing that a number of judicial procedures foster economic growth by increasing the predictability of court decisions, which leads to more transactions and higher investment levels. We investigate the effects on economic growth of 15 judicial procedures. Employing a standard growth model, we find in a cross-section of 67 countries that timeliness, writtenas opposed to oralprocedures, and the right to counsel have a positive effect on growth, whereas the number of independent procedural actions as well as the presumption of innocence have negative effects. Our results partially contradict the results of former studies based on the Lex Mundi dataset.
Keywords: H11; K40; O40; P51; 330; Judicial procedure; legal formalism; judicial independence; rule of law; investment; growth; Gerichtsbarkeit; Verfahrensrecht; Wirtschaftswachstum; Schätzung; Welt